2015
DOI: 10.5539/ijms.v7n2p90
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Effect Electronic Banking in Customer Satisfaction and Loyalty

Abstract: In order to understand customers' characteristics, banking management should create a good relationship with them. The goal of this research is evaluation of effect electronic banking and three dimensions comprise quality of system, quality of information and quality of servicein customer loyalty with regard to role of customer satisfaction among customers of mellat bank in Isfahan city in Iran. The population of the study comprises customers of mellat bank in Isfahan city that use of total electronic banking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
(29 reference statements)
1
10
0
1
Order By: Relevance
“…According to Bhatty et al (2001), true customer loyalty are driven by a strong, trusting relationship between the customer and the business. According to Aghdaie et al (2015), customer satisfaction and loyalty increases when system quality and information quality is remarkable in the banking industry. The authors further mentioned that Internet banking allows customers to be more flexible as they can access products and services 24/7 without any difficulty.…”
Section: Reliability (Rel)mentioning
confidence: 99%
“…According to Bhatty et al (2001), true customer loyalty are driven by a strong, trusting relationship between the customer and the business. According to Aghdaie et al (2015), customer satisfaction and loyalty increases when system quality and information quality is remarkable in the banking industry. The authors further mentioned that Internet banking allows customers to be more flexible as they can access products and services 24/7 without any difficulty.…”
Section: Reliability (Rel)mentioning
confidence: 99%
“…Customer satisfaction has been treated as a fundamental factor affecting customer loyalty and satisfied customers are more likely to make the same Adoption of mobile payment purchasing decision (Hossain et al, 2018). In addition, satisfaction with the loyalty base is the determining factor for a satisfactory association and customer retention (Aghdaie et al, 2015;Ammari and Bilgihan, 2017). Satisfaction is therefore the dominant factor affecting customer loyalty, accordingly, the following hypothesis is proposed: H3.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Several previous studies have stated that there is a significant relationship between internet banking and customer satisfaction and loyalty (Amin, 2016). Meanwhile, according to Aghdaie et al customer loyalty and satisfaction increase when the quality of the information system is extraordinary in the banking industry (Aghdaie et al, 2015). Musiime and Ramadhan also found that there is a relationship that is directly proportional to customer loyalty and internet banking (Musiime & Ramadhan, 2011).…”
Section: Satisfaction and Loyaltymentioning
confidence: 97%